Innovative health professional leadership for a climate-resilient Bahamas - Calae D. Philippe; William M. Hamilton; Alvonee C. Penn; James M. Shultz (Elsevier, 2021)
The Commonwealth of the Bahamas recognizes the reality of climate change and its disproportionate impacts on the health and welfare of small island states. Therefore, The Bahamas is partnering with the Caribbean Community, the Pan American Health Organization (PAHO)/World Health Organization (WHO), the Green Climate Fund, European Union, United Nations, and other regional and international organizations to confront the climate crisis. The Bahamas is strategizing solutions to combat climate risks to human and environmental health including sea level rise, temperature anomalies, precipitation extremes, and weather-related disasters. Health professionals are at the forefront.We discuss current initiatives in several areas: engaging health professionals as leaders in devising green solutions, infusing health professions training with climate science, energizing the youth generation to contribute to a climate resilient Bahamas, and prioritizing mental health and psychosocial support (MHPSS) for survivors of climate disasters.